AJDODLAR MEROSI – BUYUK QADRIYAT - Ergasheva, G.M. (SCIENCE and SOCIETY, 2024)
Today, it is a great contribution to the development of our national culture, science, literature and art to study and promote the rich heritage of our enlightened ancestors, its essence special attention is paid to instilling in the consciousness of the young generation. This article, the legacy of great ancestors and was written based on the theme of glorifying national values.
Keywords: enlightened ancestors; heritage of great ancestors; glorification of national values; values in the process of education